PERBANDINGAN TINGKAT KEHALUSAN FLY ASH TERHADAP DURABILITAS DAN SIFAT MEKANIS HIGH VOLUME FINE FLY ASH-SELF COMPACTING CONCRETE - Mubarak, Fauzi; Solikin, Mochamad; Sunarjono, Sri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
Construction made from concrete, both conventional concrete and Self Compacting Concrete (SCC), which contact with seawater, often run into decreased durability due to the content of chemical compounds that are harmful for concrete, such as Magnesium Sulfate (MgSO4) and Chloride (Cl). One way to overcome this problem is to use fine fly ash in the concrete mixture. This article discusses the results of an experimental study on the use of fine fly ash in High Volume Fly Ash- Self Compacting Concrete on durability and mechanical properties. Fine fly ash used is processed using the fly ash filtering method with a water filter. The research method is a laboratory experiment by making concrete test objects. Durability tests include Volume of Permeable Voids (VPV) and Rapid Chloride Penetration Test (RCPT), while mechanical properties is concrete compressive strength. The research results showed that using fine fly ash compared to concrete without fly ash or concrete with raw fly ash positively impacted increasing compressive strength, reducing concrete voids, and good resistance to chloride attack at low penetration levels.